2021
DOI: 10.2478/bhee-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Test Program Framework for Non-Sf6 Switching Gases

Abstract: In recent years, significant achievements have been made with respect to the development of SF6-free gas insulated substations (GIS). In parallel, the interest in installing SF6-free GIS by utilities increased steadily and tenders for new substations or upgrades, which regularly also include alternative technologies. The excellent performance of SF6 was unequivocally accepted by all vendors and users so that the community became used to single technology solutions. This is no longer the case with alternative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…À 10.5 °C. 19 F NMR (377 MHz, neat, external [D 6 ]acetone, 21 °C): δ (ppm) = 66.1 (m, 4F B , 2 J( 19 F B , 19 F A ) = 153.1 Hz, 4 J( 19 F B , 19 F CF ) = 10.0 Hz), 58.9 (m, 1F A , 2 J( 19 F A , 19 F B ) = 153.1 Hz, 4 J( 19 F A , 19 F CF ) = 1.4 Hz), À 59.5 (dquint, 3F, OCF 3 , 4 J( 19 F A , 19 F CF ) = 1.4 Hz, 4 J( 19 F B , 19…”
Section: Reagents and Analytical Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…À 10.5 °C. 19 F NMR (377 MHz, neat, external [D 6 ]acetone, 21 °C): δ (ppm) = 66.1 (m, 4F B , 2 J( 19 F B , 19 F A ) = 153.1 Hz, 4 J( 19 F B , 19 F CF ) = 10.0 Hz), 58.9 (m, 1F A , 2 J( 19 F A , 19 F B ) = 153.1 Hz, 4 J( 19 F A , 19 F CF ) = 1.4 Hz), À 59.5 (dquint, 3F, OCF 3 , 4 J( 19 F A , 19 F CF ) = 1.4 Hz, 4 J( 19 F B , 19…”
Section: Reagents and Analytical Techniquesmentioning
confidence: 99%
“…[3,18] In addition, they must be safe to use, harmless to the used infrastructure and facilitate a well-known industrial handling. [2,19] Furthermore, specific intrinsic and extrinsic properties are required, including basic chemical and physical properties like high dielectric strength (DS), low boiling point and suitable reactivity, including the formation of harmless by-products. [2,13,20] The required high dielectric strength depends on the ability to absorb free electrons and to form anions and thus on the compound-related electron affinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer some of these questions, the High Voltage Laboratory at ETH Zurich has launched a project with the aim of comparing available SF 6 gas alternatives. Planned research activities are shown in the publication by Franck et al [1].…”
Section: Introductionmentioning
confidence: 99%